Mecanismo de acción de los productos lipoxigenados sobre la esteroidogénesis - Leone, María Eugenia (2016)
Hormonal regulation of steroidogenesis involves arachidonic acid, precursor of the lipoxygenated products necessary for activation of steroidogenesis, irrespective of the stimulus that triggers the response. In other systems, it is postulated that lipoxygenated metabolites of arachidonic acid are secreted and they would act in an autocrine fashion stimulating a membrane receptor called OXER1. This protein belongs the G protein-coupled receptors with high affinity for 5-oxo-ETE, 5-HPETE and 5- HETE, products of 5-lipoxygenase. Based on this background, we hypothesized that the metabolites of arachidonic acid via the 5-LOX could signal through their own receptor in the regulation of steroidogenesis. In order to identify OXER1 as mediator of the activation of steroidogenesis, initially, we demonstrated the presence of OXER1 receptor in H295R human steroidogenic cells. Then, we modified the activity and the expression of OXER1 in steroidogenic cells. The activity was pharmacologically modified, using an agonist and an antagonist of the receptor. These compounds were able to modify steroid production by H295R cells. In order to modify the expression levels, first we needed to obtain molecular biology tools. So, a specific RNAi was introduced in a pSUPER.retro.puro plasmid and the human cDNA was cloned in pRc/CMVi and pBABE. MA-10 Leydig mouse testis cells and/or H295R human adrenocortical cells were transfected with these constructions. Only the two recombinant plasmids obtained for overexpression were functional as only in these cases the expected change in OXER1 expression (mRNA and/or protein) was achieved. To verify the performance of overexpressed OXER1, we determined the effect of transfection of both plasmids on steroid production in both MA-10 and H295R cells. The stimulation of these cells by agonists that activate signaling pathways that involve both cAMP/PKA and PLC/PKC resulted in an increase in steroidogenesis when OXER1 was overexpressed. Thus, here we presented evidence for the involvement of the membrane receptor OXER1 in the activation of steroid production. Another important contribution of this work is that transfection of cells H295R human adrenocortical cells generated cells that stably express the OXER1. This new cell line, H295R-OXER1, will be a useful tool in future analysis of the signal transduction pathways involved in the activation of the receptor.